Larvae of migratory Characiformes species in an archipelago in the Lower Amazon River - Lucas Silva de Oliveira (Acta Scientiarum. Biological Sciences, 2021)
In the Amazon basin, most of the migratory Characiformes species represent an important fishing resource for local people. However, the lack of information about the main areas and periods of reproduction and the importance of certain environments for the maintenance of species may jeopardize the renewal of fish stocks. Thus, the aim was to examine the spatial and seasonal variation in the density of larvae of migratory Characiformes species in an archipelago in the Lower Amazon River and to assess the importance of this environment for the biological recruitment of the studied species. The capture of larvae was carried out in places close to restinga swamps, steep ruts, and inlet areas with a plankton net (300 µm) in monthly sampling from January to December 2013. An analysis of variance was used to verify differences in larval density between seasons and sampling months. A total of 30,997 larvae were captured and showed no significant differences in their distributions between habitats. However, a variation between the phases of the hydrological cycle was evident, in which the highest larval concentrations were observed during the flooding (17.72 larvae.10m-3) and the drought (1.33 larvae.10m-3). The study area has a great capacity to assist in the maintenance and renewal of regional fish stocks, as it is an important retention and nursery site for larvae of Characiformes that drift along the main channel of the Amazon River.